Oral ketone esters acutely improve myocardial contractility in post-hospitalized COVID-19 patients: A randomized placebo-controlled double-blind crossover study - Wodschow, Helena Zander; Davidovski, Filip Søskov; Christensen, Jacob; Lassen, Mats Christian Højbjerg; Skaarup, Kristoffer Grundtvig; Nygaard, Hanne; Møller, Niels; Rungby, Jørgen; Biering-Sørensen, Tor; Rossing, Peter; Jensen, Nicole Jacqueline; Laursen, Jens Christian (Frontiers in Nutrition, 2023)
Background COVID-19 is associated with subclinical myocardial injury. Exogenous ketone esters acutely improve left myocardial function in healthy participants and patients with heart failure, but the effects have not been investigated in participants previously hospitalized for COVID-19. Methods This is a randomized placebo-controlled double-blind crossover study comparing a single oral ketone ester dose of 395 mg/kg with placebo. Fasting participants were randomized to either placebo in the morning and oral ketone ester in the afternoon or vice versa. Echocardiography was performed immediately after intake of the corresponding treatment. Primary outcome was left ventricular ejection fraction (LVEF). Secondary outcomes were absolute global longitudinal strain (GLS), cardiac output and blood oxygen saturation. Linear mixed effects models were used to assess differences. Results We included 12 participants previously hospitalized for COVID-19 with a mean (±SD) age of 60 ± 10 years. The mean time from hospitalization was 18 ± 5 months. Oral ketone esters did not increase LVEF between placebo and oral ketone ester [mean difference: −0.7% (95% CI −4.0 to 2.6%), p = 0.66], but increased GLS [1.9% (95% CI: 0.1 to 3.6%), p = 0.04] and cardiac output [1.2 L/min (95% CI: −0.1 to 2.4 L/min), p = 0.07], although non-significant. The differences in GLS remained significant after adjustment for change in heart rate (p = 0.01). There was no difference in blood oxygen saturation. Oral ketone esters increased blood ketones over time (peak level 3.1 ± 4.9 mmol/L, p < 0.01). Ketone esters increased blood insulin, c-peptide, and creatinine, and decreased glucose and FFA (all p ≤ 0.01) but did not affect glucagon, pro-BNP, or troponin I levels (all p > 0.05). Conclusion In patients previously hospitalized with COVID-19, a single oral dose of ketone ester had no effect on LVEF, cardiac output or blood oxygen saturation, but increased GLS acutely. Clinical trial registration https://clinicaltrials.gov/, identifier NCT04377035.